No one has answered it correctly
let a = x^2
b = y^2
x+y^2 = 31 ..1
x^2+y = 41... 2
from 1
x= 31-y^2
so (31-y^2)^2 + y = 41
or 961-62y^2+y^4+y = 41
or y^4-62y^2+y+920 = 0
y if real is a factro or 920
1,2,4,5
by trial and error y =5 makes it zero
y(1) and Y(2) are too high try 4 and 5
so b = 25 and a = 36
this is answer
2006-11-25 18:45:20
·
answer #1
·
answered by Mein Hoon Na 7
·
0⤊
0⤋
"sqrt(x)" will represent "the square root of x."
Given:
sqrt(a+b)=31.
Square both sides of the eq'n. Then,
a+b=961
a=961-b
Substitute this value into the first given eq'n:
961 - b + sqrt(b) = 41
A little bit of algebra and:
b - sqrt(b) - 920 = 0
Let sqrt(b) = x. Then,
x^2 - x - 920 = 0.
Use the quadratic formula on the above eq'n (omitted here).
x = (1 +/- 3 sqrt(409)) / 2
However, since x = sqrt(b), x > 0 (I'm assuming 'a' and 'b' are real #s and that you can't have a negative square root). So,
sqrt(b) = 1/2 + 3 sqrt(409) / 2.
b = (3 * sqrt(409) + 1) ^ 2 / 4
Recall that a = 961 - b, so
a = 81/2 - 3 sqrt(409)/2
Not a nice problem...
:-(
2006-11-25 13:03:09
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
1) a+b=31^2=961
2) a+âb=41
2) b=41^2-82a+a^2
1)and 2) a+1681-82a+a^2=961
a^2 - 81a + 720=0
a=70.83 or 50.915 and
b=889.83 or 98.34 respectively
But when a is 50.915 then â98.34 is -9.9
which works for a+âb. But does not work for
â(a+b)=31
Then 70.83 and 889.83 work for â(a+b)=31
a+âb when â889.83=-29.83 So I'll
go with 70.83 and 889.83 for a and b respectively
using the negative square root of b for a+âb
2006-11-25 13:44:16
·
answer #3
·
answered by albert 5
·
0⤊
0⤋
a=36 b=25
2006-11-25 13:05:55
·
answer #4
·
answered by bj 2
·
0⤊
0⤋
The question is worded ambiguously, I assume the system is:
a+sqrt(b)=41 and sqrt(a)+b=31.
If so, the answer set is: a = 36, b = 25.
If, instead, the system is supposed to be
a+sqrt(b)=41 and sqrt(a+b)=31,
then the answer set is:
a = -sqrt(1841/2 + 3/2*sqrt(409)) + 41, b = 1841/2 + 3/2*sqrt(409), or as a decimal, a = 10.16437738, b = 950.8356226
2006-11-25 13:01:02
·
answer #5
·
answered by math_guy112358 1
·
0⤊
1⤋
b=(41-a)^2
=1681-82a+a^2
=1681-82a+a^2
a=(31-b)^2
=961-62b+b^2
substituting the value of a in the first equation b can be found and then by substitution a can be found
2006-11-25 12:58:00
·
answer #6
·
answered by raj 7
·
0⤊
0⤋
a+(b)^1/2=41 so a=41-(b)^1/2 substitute in (a)^1/2+b=31 then get roots of b using -b+-(b^2-4ac)^1/2/2a then u get 2 values for b then substitute to get values of a
2006-11-25 13:03:51
·
answer #7
·
answered by arivali 1
·
0⤊
0⤋
a*sqrt(b)=41
a^2b=1681
sqrt(a+b)=31
a+b=961
b=961-a
a^2(961-a)=1681
-a^3+961a^2-1681=0
a^3-961a^2+1681=0
There will be at least 1 real root. I don't have the patience to find it. Once you have it, substitute in
b=961-a
2006-11-25 13:02:22
·
answer #8
·
answered by yupchagee 7
·
0⤊
0⤋
a+sqr(b)=41
sqr(a+b)=31
square both side in equation 2:
a+b=961
b=961-a
sub 961-a for b in equation 1
a+sqr(961-a)=41
subtrac a from both sides
sqr(961-a)=41-a
square both sides
961-a=1681-82a+a^2
subtract 961 from both sides
-a=720-82a+a^2
add a from both sides
0=720-81a+a^2
use quad formula to solve for a and sub what you get for a to solve for b
2006-11-25 13:00:02
·
answer #9
·
answered by 7
·
0⤊
0⤋
a=36,b=25.
2006-11-25 13:06:27
·
answer #10
·
answered by Swetha C 1
·
0⤊
0⤋